2022
DOI: 10.47577/teh.v2i3.7418
|View full text |Cite
|
Sign up to set email alerts
|

contribution of ICTs to the Down Syndrome Children’s Language and Cognitive Development

Abstract: Down syndrome is considered to be one of the most prevalent genetic causes of intellectual disability, derived from chromosomal disorder, which accounts for dysfunctions in many organs and has a characteristic phenotype, which consists of physical and behavioral features. Many studies have shown that language is one of the most impaired areas of function in Down syndrome and perhaps, the highest barrier for their substantial inclusion into formal education and community. The aim of this paper is to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Further studies need to investigate the differences between self-reported and proxy reported QoL in this population. This review encourages the use of innovative technology tools such as the Smart Angel system, which uses a cloud-based support and monitoring system [ 129 , 130 ] to obtain self-reported QoL data in adults with DS, as this would encourage inclusion in society.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies need to investigate the differences between self-reported and proxy reported QoL in this population. This review encourages the use of innovative technology tools such as the Smart Angel system, which uses a cloud-based support and monitoring system [ 129 , 130 ] to obtain self-reported QoL data in adults with DS, as this would encourage inclusion in society.…”
Section: Discussionmentioning
confidence: 99%